2020
DOI: 10.22159/ijap.2020.v12s1.ff020
|View full text |Cite
|
Sign up to set email alerts
|

Elastase Activity Inhibition by the Most Active Fraction of Star Fruit (Averrhoa Carambola L.) Leaves From Three West Java Regions

Abstract: Objective: Premature skin aging is caused by increased elastase proteolytic activity, which causes elastin breakdown and disorganization in connectivetissue, reducing elasticity and flexibility, and wrinkling skin. Natural compounds in plants, especially polyphenols, inhibit elastase proteolyticactivity and prevent premature skin aging. Star fruit (Averrhoa carambola L.) leaves contain many polyphenols with antioxidant, anti-inflammatory,hypoglycemic, and antimicrobial activities. However, no studies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Moreover, polyphenols in a sample will interact with the amino acids of the enzyme such as serine, histamine, and aspartate residues through hydrogen bonds, causing a decrease in catalytic activity and denaturation of the enzyme (Brás et al, 2010;Mardhiyah et al, 2020). The presence of flavonoid polyphenols in the extract and fractions of the M. calabura allows for a role in providing anti-elastase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, polyphenols in a sample will interact with the amino acids of the enzyme such as serine, histamine, and aspartate residues through hydrogen bonds, causing a decrease in catalytic activity and denaturation of the enzyme (Brás et al, 2010;Mardhiyah et al, 2020). The presence of flavonoid polyphenols in the extract and fractions of the M. calabura allows for a role in providing anti-elastase activity.…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH radical scavenging activity (DRSA) was examined using the modified microplate method [22,23]. DPPH was dissolved in methanol (6 mg/100 ml), and 180 µl was added to extracts 20 µl (final conc.…”
Section: Determination Of Anti-oxidantmentioning
confidence: 99%
“…21 Research conducted by Mardhiyah et al, 2020 reported that the water fraction of A. carambola Depok leaves with a total polyphenol and flavonoid content of 115.68 mg gallic acid equivalent g extract and 9.15 mg equivalent quercetin / g extract can inhibit proteolytic activity elastase and prevent premature skin aging. 2 Based on the result on this research on elastase inhibitory activity, total flavonoid and total polyphenol content, it is considered that Faloak stem bark extract can be considered as potential to be developed as active compound in anti-aging product, both in cosmetic and pharmaceutical dosage forms.…”
Section: Determination Of Total Flavonoids and Total Polyphenolmentioning
confidence: 99%
“…The higher the total polyphenol content and total flavonoid levels, the higher the activity inhibition against elastase. 2 Elastase is an enzyme that is responsible for the breakdown of elastin. 3 Misregulation of the elastase enzyme is involved in the skin aging process.…”
Section: Introductionmentioning
confidence: 99%